The effect of pomegranate peel extract and apple cider vinegar as an irrigants in disinfecting the necrotic primary root canal - Anas Mando; Mohannad Laflouf; Hassan Achour; Samar Ali Alsalameh; Yasser Alsayed Tolibah (Scientific Reports)
Abstract This in-vivo study aims to assess pomegranate peel extract (PPE) and Apple Cider Vinegar (ACV) efficacy in disinfecting the necrotic primary teeth root canals. Forty-five primary incisors in thirty children. The treatment was performed under local anesthesia with rubber dam isolation. Sterile paper points were inserted for 60 s to collect the first bacterial swab (S1). Root canal walls were prepared and irrigated with 22 mL within 5 min according to the following groups (randomly with 1:1:1 allocation ratio): Group A: (n = 15) with 5% PPE, Group B: (n = 15) with 5% ACV, and Group C: (n = 15) with 5% sodium hypochlorite (NaOCl). Canals were dried with paper points, and paper point was placed in each canal for 60 s to collect the second bacterial swab (S2). Bacterial colonies were counted after 48-hour incubation at 37 °C and the bacterial counts in the S1 and S2 for each sample were compared using the decimal logarithm. Intra-group comparisons were made using Paired sample t and Wilcoxon signed ranks tests. Between-groups comparisons were made using One-Way ANOVA, Kruskal-Wallis, Mann-Whitney U, and Independent Samples tests. The significance level was set at α = 0.05. PPE demonstrated a 60.43% reduction in CFU count, ACV demonstrated a 51.56% reduction in CFU count, while NaOCl showed an 87.49% reduction in CFU count. Although NaOCl has shown effectiveness in reducing bacterial counts, PPE and ACV have also displayed some antibacterial activity. However, their overall efficacy is less established, which raises questions about their viability as a natural alternative to a 5% NaOCl.